Experimental research and evaluation of thermal camouflage effectiveness of advanced materials for mobile vehicles - Tran , Tien Bao; Tống, Minh Hòa (Journal of Military Science and Technology, 2025)
Mobile vehicles, with high heat-generating engines and metallic outer shells known for their significant heat absorption and emission, are easily detected and identified by thermal imaging reconnaissance systems. To mitigate thermal contrast, a practical solution is to apply coatings capable of reducing thermal emissions from mobile vehicles. However, no domestic studies have yet evaluated the effectiveness of thermal camouflage coatings for such vehicles. This paper focuses on analyzing the composition of advanced coating materials, conducting experimental trials, and assessing their thermal camouflage effectiveness for mobile vehicles in Vietnam. The findings of this study serve as a foundation for developing new materials and effectively applying thermal camouflage to mobile vehicles in the country.